GABAB receptor-mediated inhibition of tetrodotoxin-resistant GABA release in rodent hippocampal CA1 pyramidal cells - Jarolimek, Wolfgang; Misgeld, Ulrich (The journal of neuroscience, 1997)
Tight-seal whole-cell recordings from CA1 pyramidal cells of rodent hippocampus were performed to study GABAB receptor-mediated inhibition of tetrodotoxin (TTX)-resistant IPSCs. IPSCs were recorded in the presence of TTX and glutamate receptor antagonists. (R)-(−)-baclofen reduced the frequency of TTX-resistant IPSCs by a presynaptic action. The inhibition by (R)-(−)-baclofen was concentration-dependent, was not mimicked by the less effective enantiomer (S)-(+)-baclofen, and was blocked by the GABAB receptor antagonist CGP 55845A, suggesting a specific effect on GABAB receptors. The inhibition persisted in the presence of the Ca2+ channel blocker Cd2+. There was no requirement for an activation of K+conductances by (R)-(−)-baclofen, because the inhibition of TTX-resistant IPSCs persisted in Ba2+ and Cd2+. Because the time courses of TTX-resistant IPSCs were not changed by (R)-(−)-baclofen, there was no evidence for a selective inhibition of quantal release from a subgroup of GABAergic terminals. (R)-(−)-baclofen reduced the frequency of TTX-resistant IPSCs in guinea pigs and Wistar rats, whereas the inhibition was much smaller in Sprague Dawley rats. In Cd2+ and Ba2+, β-phorbol-12,13-dibutyrate and forskolin enhanced the frequency of TTX-resistant IPSCs. Only β-phorbol-12,13-dibutyrate reduced the inhibition by (R)-(−)-baclofen. We conclude that GABABreceptors inhibit TTX-resistant GABA release through a mechanism independent from the well known effects on Ca2+ or K+ channels. The inhibition of quantal GABA release can be reduced by an activator of protein kinase C.
Im Text ist das letzte "B" von GABAB tiefgestellt
Gesehen am 27.04.2021